Aspects of reproductive biology of the lesser spiny eel Macrognathus aculeatus (Bloch, 1786) from river Ganga, Uttar Pradesh, India - Faridi, Aysha Aziz; Bano, Farah; Serajuddin, Mohammad (Indian Journal of Fisheries, 2020)
A total of 315 samples of Macrognathus aculeatus (Bloch, 1786) were collected for this study from the river Ganga at Sant Ravidas Nagar, Bhadohi, Uttar Pradesh during June 2016 to May 2017. Chi-square test (Ï‡2) confirmed that the male to female sex ratio was 1:0.93 which was not significantly different from hypothetical ratio of 1:1. The maximum numbers of stage IV gonads were encountered during the month of June indicated its spawning period. Mass and length ratio showed a negative allometric growth (b